COVID-19 and social distancing: pandemic has altered social relationships and contacts in older adults over 4 years - Kastner, Lydia; Suenkel, Ulrike; von Thaler, Anna-Katharina; Eschweiler, Gerhard W.; Dankowski, Theresa; Mychajliw, Christian; Brockmann, Kathrin; Heinzel, Sebastian; Thiel, Ansgar (Frontiers in Public Health, 2024)
IntroductionSocial isolation is a main risk factor for loneliness, health issues and psychological diseases. With its restriction measures, the coronavirus pandemic has led to an objective reduction in meaningful interactions, communication, and social contacts in general (social isolation). However, it has been shown that older adults cope differently with social isolation. Therefore, the aim of the present study was to investigate the changes of social contacts of older adults over the pandemic period of 4 years.MethodsFor this purpose, N = 175 older adults (Mage = 72.60, SDage = 6.12 years, Mdnage = 72, Range: 60–87 years) were asked at 3 time points (2019, 2021, 2023) with how many people they had contact in the reference month (May, November). In addition to the number of contacts, participants were also asked about the type of the relationship (e.g., family, friends, neighbors), the type of contact (e.g., telephone, video conference and/or by written messages) and the emotional closeness (close, medium, low). We used an ego-centered “social network” circle to measure social contacts of older adults before, during and after the pandemic. The data collection was limited by the changing corona restrictions.ResultsResults indicate that behavior in social contacts essentially depends on age, gender, and level of depression. We found a clear temporal drop in social contacts independently of age and gender during the pandemic. After the pandemic close contacts did not recover to prepandemic level. Especially, Young-Old (<72 years) recovered less in terms of the number of social contacts than the Old-Old (≥72 years).DiscussionOur study, thus, provides longitudinal insights into the course of social contacts and suggests that social isolation may have more negative and long-term impact on close contacts, which need further clarification and temporal extension.